Eficiência na atratividade de ninhos-armadilhas para abelhas-sem ferrão (Hymenoptera, Meliponini) - CARLO BENETTI (2025)
The use of trap nests is an effective strategy for capturing stingless bee colonies, contributing both to their conservation and the improvement of meliponiculture. This study evaluated the efficiency of different trap volumes and attractant fixation techniques, as well as the impact of using vegetal paper on bait attractiveness. The experiment was conducted between 2023 and 2024 in a Cerrado fragment in the city of Rondonópolis, Mato Grosso, Brazil, using 90 traps modified with vegetal paper. Bee visits were monitored throughout the bait exposure period, also considering events such as nest construction. No trap resulted in colony capture, but 44 bee visits were recorded from the species Tetragona quadrangula (n=33), Trigona sp. (n=6), Apis mellifera (n=3), and Tetragonisca angustula (n=2). The 1.5 L and 5 L traps exhibited greater visitor diversity. The presence of vegetal paper did not significantly influence species composition (R=-0.002; p=0.848), whereas trap volume had a significant effect (R=0.006; p=0.03). Larger traps (5 L) were the most visited, followed by smaller ones (1.5 and 2 L) (ANOVA, p